Uncomfortable conversations with a Jew - Acho, Emmanuel; Tishby, Noa, 1977- (Simon Element, 2024)
For Emmanuel Acho and Noa Tishby no question about Jews is off-limits. They go there. They cover Jews and money. Jews and power. Jews and privilege. Jews and white privilege. The Black and Jewish struggle. Emmanuel asks, Did Jews kill Jesus? To which Noa responds, "Why are Jewish people history's favorite scapegoat?" They unpack Judaism itself: Is it a religion, culture, a peoplehood, or a race? And: Are you antisemitic if you're anti-Zionist? The questions, and answers, might make you squirm, but together, they explain the tropes, stereotypes, and catalysts of antisemitism in America today. The topics are complicated and Acho and Tishby bring vastly different perspectives. Tishby is an outspoken Israeli American. Acho is a mild-mannered son of a Nigerian American pastor. But they share a superpower: an uncanny ability to make complicated ideas easy to understand so anyone can follow the straight line from the past to our immediate moment, and then see around corners. Acho and Tishby are united by the core belief that hatred toward one group is never isolated: if you see the smoke of bigotry in one place, expect that we will all be in the fire.